Gothic literature a Gale critical companion - Bomarito, Jessica 1975- (Gale critical companion, 2006)
Spans all facets of gothic literature, including visual and performing arts, society and culture, themes, and settings. Includes primary source documents and critical material to provide a contextual perspective, a related chronology of key events, full-text commentaries, and lists of further readings.